Beyond the Market: The Role of Constitutions in Health Care System Convergence in the United States of America and the United Kingdom. Issue 4 (2014) - Fletcher, Jamie; Marriott, Jane
Abstract : Two narratives have emerged to describe recent health care reforms in the United States of America (US) and the United Kingdom (UK). One narrative speaks of revolution, that the adoptions of the Affordable Care Act 2010 (ACA) in the US, and the Health and Social Care Act 2012 (HSCA) in the UK, have resulted in fundamental, large-scale philosophical, political and legal change in the jurisdictions' respective health care systems. The other narrative evokes evolution, identifying each new legislative scheme as a natural development of existing governance structures. Policymakers in both the US and UK face the problem of a health care system which, as traditionally envisaged, cannot offer universal access to health care at a reasonable, or politically acceptable, price